1983
DOI: 10.1080/11250008309439448
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-fracture study of the Gregarine trophozoite: I the top of the epicyte folds

Abstract: The fine organization of the "membrane complex" present at the tip of the epicyte folds in the sporozoan Greguritia trophozoite has been studied. Electron microscopy revealed bundles of intermcdiate filaments (8-10 nm) in the interspace between plasma and middle membrane. Doublets of filaments are present in the cytoplasm adhering to the i n n s membrane. The narrow space between the inner and middle membrane exhibits electron dense dots arranged in pairs. Freeze-fracture replicas reveal a different organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It could be expected that enigmatic 12-nm filaments, running under the IMC and exhibiting the properties of intermediate filaments [ 34 , 39 ], could support the actomyosin motor in a similar way. Longitudinal arrays of IMP found in the area of the 12-nm filaments and the rippled dense structures [ 11 , 22 , 30 , 40 ] are comparable to the lines of higher particle density overlaying the subpellicular microtubules in Eimeria or Plasmodium sporozoites [ 41 , 42 ]. Our data show, however, that the number of 12-nm filaments does not influence the speed of gregarine gliding (up to 7 filaments in G. cuneata vs. 10 filaments in G. polymorpha and maximally 4 filaments in G. steini ), but rather seem to control the direction of movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be expected that enigmatic 12-nm filaments, running under the IMC and exhibiting the properties of intermediate filaments [ 34 , 39 ], could support the actomyosin motor in a similar way. Longitudinal arrays of IMP found in the area of the 12-nm filaments and the rippled dense structures [ 11 , 22 , 30 , 40 ] are comparable to the lines of higher particle density overlaying the subpellicular microtubules in Eimeria or Plasmodium sporozoites [ 41 , 42 ]. Our data show, however, that the number of 12-nm filaments does not influence the speed of gregarine gliding (up to 7 filaments in G. cuneata vs. 10 filaments in G. polymorpha and maximally 4 filaments in G. steini ), but rather seem to control the direction of movement.…”
Section: Discussionmentioning
confidence: 99%
“…King and Sleep [ 15 ] estimated that the number of myosin heads at the site of interaction in Gregarina gamonts to be in excess of 200 and showed that the gliding rate in a giant eugregarine Porospora gigantea is four times higher (up to 60 μm/s) than the speed of myosin movement along the actin filaments of a muscle sarcomere. In spite of a few freeze-etching studies that focus on the supramolecular cell organisation of some Gregarina species [ 11 , 22 , 30 ], the precise location of the actomyosin complex is as yet unknown. However, the TRAP or TgMIC2 molecules that are in contact with the substrate suggest that the concept of a glideosome might help shed light on the role of the mucus [ 12 ] in the gliding mechanism of gregarines [ 31 - 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The organization of the intramembrane particles (IMPs) at the tip of the folds has already been described (SchrCvel et al, 1983;Dallai & Vegni Talluri, 1983). Replicas of the surface of the epicytic folds show that the fracture plane cleaves either the top or the bottom of the folds ( trophozoite.…”
Section: Observationsmentioning
confidence: 99%
“…Thus, these pores, observed only in some SEM preparations, were most likely visualised due to a specific fixative osmolarity. In eugregarines, the micropores are often located at the base of the grooves between the epicytic folds, while the smaller pores are randomly distributed on the base or on the lateral side of the folds [ 3 , 17 , 18 , 78 ]. The diameter sizes of pores in S .…”
Section: Discussionmentioning
confidence: 99%